Oxidative breakage of cellular DNA by plant polyphenols: A putative mechanism for anticancer properties - Hadi, S.M.; Bhat, Showket H.; Azmi, Asfar S.; Hanif, Sarmad; Shamim, Uzma; Ullah, M.F. (Seminars in cancer biology, 2007)
Plant polyphenols are important components of human diet and a number of them are considered to possess chemopreventive and therapeutic properties against cancer. They are recognized as naturally occurring antioxidants but also act as prooxidants catalyzing DNA degradation in the presence of transition metal ions such as copper. We have shown that several of these compounds are able to bind both DNA and Cu(II) forming a ternary complex. A redox reaction of the polyphenols and Cu(II) in the ternary complex may occur leading to the reduction of Cu(II) to Cu(I), whose reoxidation generates a variety of reactive oxygen species (ROS). We have further confirmed that the polyphenol–Cu(II) system is indeed capable of causing DNA degradation in cells such as lymphocytes. We have also shown that polyphenols alone (in the absence of added copper) are also capable of causing DNA breakage in cells. Neocuproine (a Cu(I) sequestering agent) inhibits such DNA degradation. It also inhibits the oxidative stress generated in lymphocytes indicating that the cellular DNA breakage involves the generation of Cu(I) and formation of ROS. It is well established that tissue, cellular and serum copper levels are considerably elevated in various malignancies. Therefore, cancer cells may be more subject to electron transfer between copper ions and polyphenols to generate ROS. Thus, our results are in support of our hypothesis that anticancer mechanism of plant polyphenols involves mobilization of endogenous copper possibly chromatin bound copper and the consequent prooxidant action.